2 - Rulers against Writers, Writers against Rulers: The Failed Promise of the Public Sphere in Postcolonial Nigerian Fiction - Kehinde, Ayo (Africa Development, 2021)
Various literary critics have dwelt on the nature, tenets and trends of commitment in Nigeria literature. However, there is paucity of scholarly studies on the representations of the failed promise to the public sphere in postcolonial Nigerian fiction. This paper, therefore, examines the strat- egies and technicalities of representing the castrated hope of the public sphere in postcolonial Nigerian fiction, using the templates provided by Chinua Achebe’s Anthills of the Savannah, Ben Okri’s The Fam- ished Road and Chimamanda Ngozi Adichie’s Purple Hibiscus. The methodology involves a close reading of the selected texts, using Jürgen Habermas’s concept of the Public Sphere as the theoretical framework. The paper reveals that the context of the texts (Nigeria) lacks the public sphere, which is supposed to provide a liminal space between the pri- vate realm of civil society and the family, as well as the sphere of public authority. This is disclosed in the refusal of the characters to disregard ‘status altogether’ (Habermas 1991:36).